2013
DOI: 10.3390/ani3030608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Selected Factors on the Occurrence of Contact Dermatitis in Turkeys on Commercial Farms in Germany

Abstract: Simple SummaryIn two extensive field studies in Germany, the influence of husbandry on health and fitness of fattening turkeys was investigated in living animals of various ages as well as carcasses shortly after slaughter. Already in the early rearing phase, contact dermatitis of foot pads was observed as a relevant problem in turkey farming. Litter quality and condition as well as management must be coordinated at all rearing stages of turkeys to prevent the appearance of high litter moisture values in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…For more than 30 years, researchers have been investigating the impact of litter quality on the foot pad health and performance of different poultry species, including broilers [ 9 , 10 , 11 ] and turkeys [ 3 , 12 , 13 , 14 ]. Several studies suggested that there is a strong association between poor litter conditions and foot pad dermatitis [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For more than 30 years, researchers have been investigating the impact of litter quality on the foot pad health and performance of different poultry species, including broilers [ 9 , 10 , 11 ] and turkeys [ 3 , 12 , 13 , 14 ]. Several studies suggested that there is a strong association between poor litter conditions and foot pad dermatitis [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of breast injuries, it is likely that this is less visible on-farm, but later noticed at processing after defeathering (56), and is likely only of importance once carcasses are condemned for this reason (45). However, despite not being considered an issue on-farm, management practices such as, e.g., litter and floor management can contribute the occurrence of breast injuries which can cause pain and discomfort for birds (18,56). Furthermore, skin conditions including breast buttons/blisters (inflamed bursa) were actually one of the more commonly mentioned reasons for condemnation or downgrading at slaughter in the current study.…”
Section: Discussionmentioning
confidence: 68%
“…Previous work has mainly focused on identifying risk factors in the social and physical environment of the birds in efforts to improve turkey health and welfare (12,(16)(17)(18)(19). However, there is limited information available on what turkey farmers themselves consider important for turkey health and welfare (20).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we were not able to investigate the relationship of the estimated drinking behaviour traits with functional traits, such as the incidence of foot pad dermatitis (FPD). Recent studies showed that elevated litter moisture around drinkers and feeders is sufficient to increase the incidence and the severity of FPD; an increase in wet litter from 10 to 30% increased incidence of FPD [ 18 , 19 ]. If different drinking behaviour traits lead to differences in litter wetness, through for example water spillage, then one can hypothesise the existence of a correlation with the severity or incidence of FPD.…”
Section: Discussionmentioning
confidence: 99%